Análise de biomarcadores salivares em pacientes com gengivite após uso de dentifrício 1% à base de própolis vermelha brasileira: um ensaio clínico randomizado - Silva, Mônica do Amaral (2019)
Introduction: The use of natural products by the human being as a therapeutic alternative goes back to the ancient age and these products are essential in the production of new drugs, a fact that has led the researchers to seek alternatives with substances with biological activity, thus highlighting the brazilian red propolis (BRP). Studies also prove the therapeutic effect of the BRP extract on microbial inhibition of cariogenic agents, besides presenting as a clinical option of low toxicity. The presence of fixed appliances in the oral cavity may cause changes on the dental biofilm. Some salivary markers and clinical parameters may undergo changes due to orthodontic treatment and gingivitis. Objective: The objective of this study was to longitudinally evaluate the salivary biomarkers profile, total protein, amylase and IL-10, pH and salivary flow, and plaque index after use of a BRP dentifrice in patients under orthodontic treatment. In addition, to evaluate the perception of the participants regarding the sensations and possible adverse effects after the use of BRP dentifrice. Material and methods: This is a longitudinal, randomized, double-blind, controlled study. The research was approved by the Research Ethics Committee under number 2.551.395 and the participants selected in the city of Aracati-CE. For preparation of the red propolis dentifrice, a concentration of 1% was incorporated. A total of 76 participants were randomized into two groups: Group I - Red Propolis Dentifrice + 1500ppm Fluoride (n = 38), Group II - 1500ppm Fluoride Dentifrice (n = 38). Saliva samples from all participants were collected before and after 4 weeks of treatment. They were then properly maintained, transported, centrifuged and stored until analysis. The salivary total protein concentration of saliva aliquots was determined by the BCA method, using as standard a bovine serum albumin (BSA) curve, the activity of amylase and IL-10 was also evaluated using commercial kits. Patients' perceptions of propolis dentifrice use were assessed using a questionnaire. Results: Treatment with different dentifrices did not change total salivary proteins before and after treatment (G1: p = 0.0746; G2: p = 0.2144) and the pH remained similar. The activity of amylase also showed no variation in G1 (p = 0.1877) and G2 (p = 0.4674). IL-10 had a significant reduction, G1 (p <0.0001) and G2 (p = 0.03). The salivary flow of the group treated with BRP dentifrice did not show statistically significant variation (p = 0.172), as well as in the group treated with commercial fluoridated dentifrice (p = 0,329). About the perception and acceptance of the formulation with propolis, it did not cause adverse effects and had a good acceptance by the users. Conclusion: In this study, after 4 weeks of use by the participants, there were no differences between the total protein, pH and amylase markers when compared to the propolis dentifrice group with the fluoride dentifrice group. The IL-10 dosage and plaque index were reduced in the propolis dentifrice group after the period of use. Regarding perception, the BRP dentifrice was well accepted by the patients.